(untitled) (Global Journal of Human-Social Science, 2025)
The field of Public School Administration as an area of study in Brazil began to take shape in the early twentieth century. José Querino Ribeiro is widely recognized as the scholar who laid the foundational groundwork for this discipline, publishing his first book on the subject in 1938. In this seminal work, he introduced key conceptual definitions -such as those for ’administration’, ’cooperation’, and ’coordination’ -that would become central to the field. His theoretical framework was notably influenced by Henri Fayol’s general theory of administration. Querino Ribeiro’s impact on school administration in Brazil extended through the 1950s and was significantly reinforced with the publication of his landmark work Ensaio de uma teoria da administração escolar (1952), which remains one of the most influential contributions to the field. This article examines the administrative theory developed by the Brazilian scholar across two seminal works, highlighting their foundational role in establishing Public School Administration as a multidisciplinary field of research in Brazil.